High-performance memristor based on MoS2 for reliable biological synapse emulation. (August 2022) - Chen, Jianbiao; Xu, Jiangwen; Chen, Jiangtao; Gao, Liye; Yang, Chunyan; Guo, Tongtong; Zhao, Yun; Xiao, Yifeng; Wang, Jian; Li, Yan
Abstract: Inspired by the neural network of the human brain, neuromorphic emulation for memorizing and processing data using electronic devices has attracted widespread intention. The conductance of memristor device can be changed by the charge flowing through it, which is analogical to the variation of synaptic plasticity with the applied external stimulation. However, the high switch voltage and inferior stability of memristor limit the further application to the imitation of biological synapse. Here, a memristor based on large-area MoS2 with vertical structure Al/MoS2 /Cu is constructed, which is deposited by magnetron sputtering system on aluminum foil. The memristor presents superior stability and robustness, and has a small set and reset voltages with narrow variation distribution. More importantly, by applying relevant pulse sequence, the essential synaptic behaviors are mimicked by using the memristor based on MoS2, including paired-pulse facilitation (PPF) and spiking-time-dependent plasticity (STDP), etc. Graphical Abstract: ga1 Highlights: Large-area (up to A4 paper size) MoS2 film is synthesized successfully by magnetron sputtering. The Al/MoS2 /Cu memristor have excellent stability and robustness with up to 200 cycles and retention time 10 4 s. Set and reset voltage of the memristors based MoS2 are less than 0.4 V with narrow variation. Some fundamental synaptic functions are carried out successfully, including EPSC, PPF and STDP, etc.